Numerical study on the characteristics of viscous fingering during the displacement process of non-Newtonian fluid - Wu, Yu-Ting; Qin, Zhen; Ma, Huaiyu; Lyu, Sung-Ki (PloS one, 2024)
This study uses numerical methods (ANSYS-Fluent) to investigate the viscous fingering of the displaced phase as a shear-thinning fluid in the classic three-dimensional Hele-Shaw cell. Comparing the behavior of fingerings with different properties on the upper and lower surfaces of a three-dimensional model, it was found that when the upper and lower surfaces are walls, under the combined action of moving contact lines and Saffman-Taylor instability, fingering splitting occurs at the tip, resulting in the appearance of two fingers at the interface. In addition, we have found that interfacial tension has a suppressive effect on short waves. As the interfacial tension increases, the velocity at the advancing tip decreases. Therefore, when the interface tension is 0, viscous fingering displacement reaches the farthest distance. We have also conducted research on the viscous fingering at different temperatures. The results indicate that increasing the temperature leads to a decrease in the viscosity of the displaced phase, making the flow more stable. As the temperature rises, the pressure gradient inside the flow path increases, pushing the viscous fingering further.